LEGAL PROTECTION AGAINST NOTARY IN REPORTING SUSPICIOUS FINANCIAL TRANSACTIONS THROUGH GO ANTI MONEY LAUNDERING APPLICATION - Eka Nurfidyah; Irwansyah; Maskun (Awang Long Law Review, 2022)
This research is legal research that analyzes and examines the legal protection of notaries in reporting suspicious financial transactions through the Go Anti Money Laundering application. This study aims to provide legal protection for notaries in a preventive and repressive manner to create a sense of security and attitude towards a notary in carrying out his role and responsibility as a reporting party. This research method uses typeprescriptive normative research by using data on primary legal materials and secondary legal materials, which were analyzed using qualitative methods by using the theoretical basis and then presented in a comprehensive and descriptive. The results of the research show that the shape legal protection for notaries as reporting parties in reporting suspicious financial transactions, namely the presence of involvement of a notary in the ML system by applying know your customer principle with customer due diligence and enhanced due diligence in risk assessment as on preventive efforts in prevention as well sanctions and punishments as a repressive effort to resolve criminal acts or other legal actions that are against the law.